2023
DOI: 10.1038/s43705-023-00219-7
|View full text |Cite
|
Sign up to set email alerts
|

Selfish bacteria are active throughout the water column of the ocean

Abstract: Heterotrophic bacteria in the ocean invest carbon, nitrogen, and energy in extracellular enzymes to hydrolyze large substrates to smaller sizes suitable for uptake. Since hydrolysis products produced outside of a cell may be lost to diffusion, the return on this investment is uncertain. Selfish bacteria change the odds in their favor by binding, partially hydrolyzing, and transporting polysaccharides into the periplasmic space without loss of hydrolysis products. We expected selfish bacteria to be most common … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…Moreover, at both depths, HMW organic matter addition also fueled considerable bacterial growth (Figures 1 and 2). Furthermore, the observation that an enhancement in the supply of natural organic matter during a spring bloom fueled a similar response—enhancement only of selfish laminarin uptake—concurrent with widespread external hydrolysis (Giljan et al, 2023; Reintjes, Fuchs, Scharfe, et al, 2020), suggests that the responses observed in the mesocosm experiments are not an anomaly.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Moreover, at both depths, HMW organic matter addition also fueled considerable bacterial growth (Figures 1 and 2). Furthermore, the observation that an enhancement in the supply of natural organic matter during a spring bloom fueled a similar response—enhancement only of selfish laminarin uptake—concurrent with widespread external hydrolysis (Giljan et al, 2023; Reintjes, Fuchs, Scharfe, et al, 2020), suggests that the responses observed in the mesocosm experiments are not an anomaly.…”
Section: Discussionmentioning
confidence: 92%
“…Extensive selfish uptake of laminarin by Bacteroidota has previously been measured during the late stages of a phytoplankton bloom in the North Sea (Reintjes, Fuchs, Scharfe, et al, 2020). Selfish Planctomycetes have been identified in the surface waters of the Atlantic Ocean (Reintjes et al, 2017), while Verrucomicrobiota , in particular the clade Pedosphaeraceae , showed strong selfish uptake of laminarin in early summer in the North Sea (Giljan et al, 2023). Here, we found that increases in the abundance of selfish bacteria capable of laminarin uptake in amended mesocosms were occasionally the result of increases in a singular group, which varied by treatment, depth, and station.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Balmonte et al ., 2018; Reintjes et al ., 2020b). Recently, serendipitous observations of fluorescently stained cells in incubations with FLA‐PS demonstrated that the selfish mechanism plays an important role in ocean surface waters (Reintjes et al ., 2017, 2019, 2020a & 2020b) and even in the deep ocean (Giljan et al ., 2021). Either or both of these mechanisms could be used by the heterotrophic community to degrade a given polysaccharide, but the extent to which one is used can vary greatly (e.g.…”
Section: Introductionmentioning
confidence: 99%